The Relationship between Learning Agility and Innovative Work Behavior in Teachers at Senior High School X - Ariska, Fani; Candra, Ifani; Syahrina, Isna Asyri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
The ever-evolving education demands teachers to have the ability to innovate and adapt to changes in order to improve the quality of learning. Innovative work behavior demonstrated by teachers is closely related to learning agility. Learning agility is the ability to learn and adapt quickly to challenges and changes. This study aims to see whether there is a relationship between learning agility and innovative work behavior in teachers of SMA X. This study was conducted on SMA X teachers with a sample of 63 people with a quantitative research method where the subject determination technique used a total sampling technique, namely all members of the population were sampled or respondents. The measuring instrument used was the learning agility adaptation scale and the innovative work behavior adaptation scale . The results of the validity coefficient on the innovative work behavior scale ranged from 0.371 to 0.770 with a reliability coefficient of 0.860. The results of the validity coefficient on the learning agility scale ranged from 0.323 to 0.841 with a reliability coefficient of 0.916. Based on the results of the study, a correlation value of r = 0.596 was obtained with a significance level of 0.000. The hypothesis test shows a positive relationship between learning agility and innovative work behavior in high school X teachers. This finding also shows that there is a significant relationship between learning agility and innovative work behavior in high school X teachers, so the research hypothesis is accepted. This study found an effective contribution of the learning agility variable to innovative work behavior of 35.52%, which means that learning agility is able to contribute to innovative work behavior by 35.52%.